Compositional characterization and storage capacity of shale samples from La Luna and Conejo Formations (Middle Magdalena basin and the Eastern Cordillera): Implications for evaluation of cretaceous shale gas in Colombia (2015)
Shale gas has become a major non-conventional energetical resource. La Luna Formation which is commonly considered as the main petroleum source rock, have also shown to be a major reservoir for shale gas resources. In order to understand the "real" potential of this unit and define exploration strategies, the correlation between compositional and petrophysical patterns. We have analyzed 11 shale samples from La Luna and Conejo Formation in the Middle Magdalena basin and the Eastern Cordillera in order to established its composition, total organic contents, thermal maturity, as well as its total porosity and adsorption capacity. Obtained results suggest that due to its organic content, the presence of quartz and carbonate that these shales have a good quality as a gas reservoir and may have also a moderately good behavior during fracturing.